Dry-method electrode pole piece film and preparation method thereof
Through the combination of active materials with specific particle size and fibrous adhesives, combined with the optimized ratio of conductive agents and adhesives, the problem of difficult to take into account both the film forming properties and compaction density of the dry electrode sheet film is achieved, and high The electrode film with tensile strength and high compaction density improves electrical performance.
Patent Information
- Application Number
- CN202411462357.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing dry electrode sheet films are difficult to take into account both film forming properties and compaction density, resulting in an impact on electrical properties.
Using the combination of active material particles of a specific particle size and a fibrous adhesive, fibers are carried out through the adaptation of large-particle size active material particles and small-particle size active material particles, combined with the optimized ratio of conductive agents and adhesives. Chemical treatment, crushing and granulation and multi-roll continuous rolling film formation treatment to form a high tensile strength and high compaction density electrode film.
The excellent film forming properties, high compaction density and stability of the electrode film are achieved, and the electrical performance is improved.
Smart Images

Figure CN119324194A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dry electrode manufacturing, and in particular to a dry electrode pole piece membrane and a preparation method thereof. Background Art
[0002] In the prior art, the preparation of positive and negative electrode films of lithium-ion batteries is generally carried out by wet slurry coating. This wet process usually uses solvents and requires a baking and drying step, which not only has a certain negative impact on the production environment and safety, but also has the problem of high energy consumption.
[0003] Based on this, researchers proposed a dry-process electrode film preparation process, which eliminates the use of solvents in the preparation process of the electrode film. Specifically, the dry-process electrode film preparation process usually uses high-mixed fiberization of electrode powder (a mixture of positive and negative electrode main materials, adhesives and conductive agents) and then crushing and granulating, and finally rolling and calendering to obtain a dry-process electrode film. However, the dry-process electrode film prepared by the existing dry process has the problem of poor film forming properties (i.e., low tensile strength) or low compaction density, that is, it is difficult to effectively take into account the excellent film forming properties and high compaction density of the electrode film, resulting in the electrical properties of the corresponding electrode sheet being affected. Summary of the invention
[0004] The purpose of the present application is to provide a dry electrode film and a preparation method thereof, wherein the dry electrode film has both good film-forming properties and high compaction density.
[0005] The embodiment of the present application is implemented as follows:
[0006] In the first aspect, an embodiment of the present application provides a dry electrode plate film, comprising active material particles, conductive agent particles and an adhesive, wherein the adhesive is in a fibrous form, and the active material particles comprise large-size active material particles and small-size active material particles, wherein the particle size D50 of the large-size active material particles is 4 to 10 μm, and the particle size D50 of the small-size active material particles is 1 to 2 μm, and the small-size active material particles are arranged in an area close to and bonded to the adhesive along the extension direction of the adhesive.
[0007] In the above technical scheme, the active material particles are composed of large-size active material particles and small-size active material particles of specific particle sizes, the adhesive is fibrous and the small-size active material particles are arranged in the area close to and bonded to the adhesive along the extension direction of the adhesive; wherein, the large particles of the specific particle size contribute to the fiberization of the adhesive, so that the corresponding electrode film has excellent film-forming properties (i.e., has higher tensile strength); some small particles of the specific particle size close to the adhesive are filled in the gaps between the large particles, so that the electrode film has a higher compaction density, and at the same time, the small particles of the specific particle size attached to the adhesive can surround the large particles together with the fibrous adhesive, thereby increasing the binding force between the active material particles in the electrode film, so that the electrode film has higher stability.
[0008] In some optional embodiments, the particle size D50 of the large-size active material particles is 6-8 μm, and the particle size D50 of the small-size active material particles is 1-1.5 μm.
[0009] In the above technical solution, the particle size D50 of the large particle active material and the small particle active material are respectively limited to a more suitable range, so that the electrode film has a better film-forming property and a higher compaction density.
[0010] In some optional embodiments, the particle size D90 of the large-size active material particles is 15-20 μm, and the particle size D90 of the small-size active material particles is 3-4 μm.
[0011] In the above technical solution, the particle size D90 of the large particle active material and the small particle active material are respectively limited within a suitable range so that both have a suitable upper limit particle size, which also helps to improve the film forming property and compaction density of the electrode film.
[0012] In some optional embodiments, the mass of the small-size active material particles directly bonded to the binder accounts for 50-60% of the total mass of the small-size active material particles.
[0013] In the above technical solution, the mass of the small particles directly bonded to the adhesive accounts for 50-60% of the total mass of the small-particle active material particles, so that the two parts of small particles used to fill the pores between the large particles and used to enclose the large particles have an appropriate mass proportion, thereby making the electrode film have better film-forming properties, higher compaction density and better stability.
[0014] In some optional embodiments, in the active material particles, the mass ratio of the large-size active material particles to the small-size active material particles is (10-50):(50-90).
[0015] In the above technical solution, the mass ratio of large particle size to small particle size is limited to a specific range so that the two can be better compounded, thereby making the electrode film have better film forming properties, higher compaction density and better stability.
[0016] In some optional embodiments, in the electrode film, the mass ratios of the active material particles, the conductive agent particles and the binder are (90-98): (1-3): (2-5) respectively.
[0017] In the above technical solution, the mass ratio of active material particles, conductive agent particles and adhesive in the electrode film is limited to a specific range, so that the electrode film has relatively excellent electrical properties.
[0018] In some optional embodiments, the active material particles are positive electrode active material particles, and the positive electrode active material particles are selected from at least one of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel-manganese or nickel-aluminum binary material and nickel-cobalt-manganese-aluminum quaternary material.
[0019] In the above technical solution, this adaptation system with a specific particle size is particularly suitable for dry-process positive electrode film, wherein a wide variety of materials are applicable to the positive electrode active material particles, and a wide variety of feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solution provided in this application.
[0020] In some optional embodiments, the conductive agent particles are selected from at least one of carbon nanotubes, conductive carbon black, carbon fibers, conductive graphite and acetylene black; and / or the binder is selected from at least one of polyvinylidene fluoride and polytetrafluoroethylene.
[0021] In the above technical solutions, there are many types of materials that can be used for the conductive agent and the adhesive, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided in this application.
[0022] In a second aspect, an embodiment of the present application provides a method for preparing a dry electrode film as provided in an embodiment of the first aspect, comprising the following steps:
[0023] Active material particles, conductive agent particles and adhesive are mixed to obtain a mixture; and the mixture is subjected to fiberization treatment, crushing and granulation treatment and multi-roller continuous rolling film-forming treatment in sequence to obtain a dry electrode plate film.
[0024] By preparing according to the above process, a dry electrode film with good film-forming properties, high compaction density and stability can be prepared.
[0025] In some optional embodiments, the step of mixing active material particles, conductive agent particles and a binder to obtain a mixture includes: first mixing the conductive agent particles and the binder to obtain a mixture intermediate; adding active material particles to the mixture intermediate and mixing to obtain a mixture.
[0026] In the above technical solution, the conductive agent particles and the adhesive are first mixed, and then the mixed intermediate is mixed with the active material particles. This method of adding and mixing helps the conductive agent particles to better adhere to the fibrous adhesive for distribution after fiberization, thereby helping to form a more ideal conductive network.
[0027] In some optional embodiments, in the step of first mixing the conductive agent particles and the adhesive, the linear speed of the stirring paddle is 5 to 20 m / s, the stirring time is 20 to 60 min, and the processing temperature is 5 to 20°C.
[0028] In the above technical solution, in the step of mixing the conductive agent and the adhesive, the linear speed of the stirring paddle, the stirring time and the processing temperature are respectively limited within specific ranges so that the conductive agent can be more evenly distributed in the adhesive.
[0029] In some optional embodiments, in the fiberization step, the linear speed of the stirring paddle is ≥40 m / s, the stirring time is 5 to 30 min, and the treatment temperature is 60 to 80°C.
[0030] In the above technical solution, in the fiberization step, the linear speed of the stirring paddle, the stirring time and the treatment temperature are respectively limited within specific ranges to achieve a better fiberization effect of the adhesive.
[0031] In some optional embodiments, in the crushing and granulation step, the screen size in the crusher is 8-20 meshes.
[0032] In the above technical solution, in the crushing and granulation step, the specifications of the screen are limited to a specific range, which can take into account both good membrane surface quality and production continuity.
[0033] In some optional embodiments, the step of multi-roller continuous rolling film forming treatment includes: firstly performing film forming treatment on the powder obtained after crushing and granulation treatment to obtain an electrode film precursor; then performing multiple thinning treatments on the electrode film precursor in sequence, wherein the roller gap in the multiple thinning treatments gradually decreases until the thickness of the membrane reaches a preset thickness specification, thereby obtaining a dry electrode electrode film.
[0034] In the above technical solution, the thinning process is achieved through multiple thinning steps and the roller gaps of the multiple thinning steps are set to be gradually reduced, which helps to improve the thickness uniformity of the prepared electrode film. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 A schematic diagram of the structure of a dry electrode film provided in an embodiment of the present application;
[0037] Figure 2 This is an electron microscope image of a dry electrode film provided in Example 1 of the present application.
[0038] Icon: 10-dry electrode film; 100-adhesive; 200a-small-sized active material particles attached to the adhesive; 200b-small-sized active material particles close to the adhesive; 300-large-sized active material particles. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.
[0041] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values "a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".
[0042] Existing dry-process electrode film is usually difficult to have both good film-forming properties and high compaction density. After research, the inventors found that the fiberization of the adhesive is related to the particle size of the active material. Specifically, active materials with large particle sizes are more conducive to the fiberization of the adhesive, so that the prepared electrode film has better film-forming properties. However, active materials with large particle sizes have the problem of low compaction density of the formed electrode film.
[0043] Based on this, the inventors use a combination of large-particle active materials and small-particle active materials of specific particle sizes so that the corresponding electrode film can have both good film-forming properties and high compaction density.
[0044] The following is a detailed description of a dry electrode film and a preparation method thereof according to an embodiment of the present application.
[0045] In a first aspect, an embodiment of the present application provides a dry electrode film, comprising active material particles, conductive agent particles and an adhesive, wherein the adhesive is in a fibrous form, and the active material particles include large-size active material particles and small-size active material particles, wherein the particle size D50 of the large-size active material particles is 4 to 10 μm (for example, but not limited to, the particle size D50 is any one of 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm, or a range value between any two of them), and the particle size D50 of the small-size active material particles is 1 to 2 μm (for example, but not limited to, the particle size D50 is any one of 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm and 2 μm, or a range value between any two of them), and the small-size active material particles are arranged in an area close to and bonded to the adhesive along the extension direction of the adhesive.
[0046] In the present application, the active material particles are composed of large-size active material particles and small-size active material particles of specific particle sizes, the adhesive is fibrous and the small-size active material particles are arranged in the area close to and bonded to the adhesive along the extension direction of the adhesive; wherein, the large particles of the specific particle size contribute to the fiberization of the adhesive, so that the corresponding electrode film has excellent film-forming properties (i.e., has higher tensile strength); some small particles of the specific particle size close to the adhesive are filled in the gaps between the large particles, so that the electrode film has a higher compaction density, and at the same time, the small particles of the specific particle size attached to the adhesive can surround the large particles together with the fibrous adhesive, thereby increasing the binding force between the active material particles in the electrode film, so that the electrode film has higher stability.
[0047] In order to better understand the technical solution, the structural schematic diagram of the dry electrode film 10 is used for auxiliary explanation. Figure 1 , wherein 100 represents a fibrous adhesive, 200a represents small-sized active material particles attached to the adhesive, 200b represents small-sized active material particles close to the adhesive, and 300 represents large-sized active material particles.
[0048] As an example, the particle size D50 of the large-size active material particles is 6 to 8 μm (for example, but not limited to, the particle size D50 is any point value among 6 μm, 6.5 μm, 7 μm, 7.5 μm and 8 μm, or a range value between any two of them), and the particle size D50 of the small-size active material particles is 1 to 1.5 μm (for example, but not limited to, the particle size D50 is any point value among 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm and 1.5 μm, or a range value between any two of them).
[0049] In this embodiment, the particle sizes D50 of the large particle active material and the small particle active material are respectively limited to a more suitable range, so that the electrode film has a better film-forming property and a higher compaction density.
[0050] As an example, the particle size D90 of the large-size active material particles is 15 to 20 μm (for example, but not limited to, the particle size D90 is any point value among 15 μm, 16 μm, 17 μm, 18 μm, 19 μm and 20 μm, or a range value between any two of them), and the particle size D90 of the small-size active material particles is 3 to 4 μm (for example, but not limited to, the particle size D90 is any point value among 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm and 4 μm, or a range value between any two of them).
[0051] In this embodiment, the particle size D90 of the large particle active material and the small particle active material are respectively limited to a suitable range so that both have a suitable upper limit particle size, which also helps to improve the film forming property and compaction density of the electrode film.
[0052] As an example, the mass of the small-size active material particles directly bonded to the binder accounts for 50-60% of the total mass of the small-size active material particles, for example but not limited to any one of 50%, 52%, 54%, 56%, 58% and 60% of the total mass or a range between any two of them.
[0053] In this embodiment, the mass of the small particles directly bonded to the adhesive accounts for 50-60% of the total mass of the small-particle active material particles, so that the two parts of small particles used to fill the pores between the large particles and used to enclose the large particles have an appropriate mass proportion, thereby making the electrode film have better film-forming properties, higher compaction density and better stability.
[0054] As an example, in the active material particles, the mass ratio of large-size active material particles to small-size active material particles is (10-50):(50-90), for example but not limited to any one of 10:90, 20:80, 30:70, 40:60 and 50:50 or a range between any two of them.
[0055] In this embodiment, the mass ratio of large particle size to small particle size is limited to a specific range so that the two can be better compounded, thereby making the electrode film have better film forming properties, higher compaction density and better stability.
[0056] It should be noted that the mass proportion of each functional component in the electrode membrane is not limited and can be adaptively adjusted according to actual needs.
[0057] As an example, in the electrode film, the mass ratios of active material particles, conductive agent particles and adhesive are (90-98): (1-3): (2-5) respectively.
[0058] In this embodiment, the mass ratio of active material particles, conductive agent particles and adhesive in the electrode film is limited to a specific range, so that the electrode film has relatively excellent electrical properties.
[0059] As an example, the active material particles are positive electrode active material particles, and the positive electrode active material particles are selected from at least one of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel-manganese or nickel-aluminum binary material and nickel-cobalt-manganese-aluminum quaternary material.
[0060] In this embodiment, this specific particle size adaptation system is particularly suitable for dry-process positive electrode film, wherein the positive electrode active material particles can be applied to a wide variety of materials and can provide a wide variety of feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in this application.
[0061] As an example, the conductive agent particles are selected from at least one of carbon nanotubes, conductive carbon black, carbon fibers, conductive graphite and acetylene black; and / or the adhesive is selected from at least one of polyvinylidene fluoride and polytetrafluoroethylene.
[0062] In this embodiment, there are many types of materials that can be used for the conductive agent and the adhesive, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solution provided in this application.
[0063] It should be noted that the functional components not specially described or limited in the dry electrode film can be arranged according to the conventional selection in the art.
[0064] In the second aspect, an embodiment of the present application provides a method for preparing a dry electrode plate membrane as provided in the embodiment of the first aspect, comprising the following steps: mixing active material particles, conductive agent particles and a binder to obtain a mixture; and sequentially performing fiberization treatment, crushing and granulation treatment and multi-roll continuous rolling film-forming treatment on the mixture to obtain a dry electrode plate membrane.
[0065] In the present application, by preparing according to the above process, a dry electrode film with good film-forming properties, high compaction density and stability can be prepared.
[0066] As an example, the steps of mixing active material particles, conductive agent particles and a binder to obtain a mixture include: first mixing the conductive agent particles and the binder to obtain a mixture intermediate; adding active material particles to the mixture intermediate and mixing to obtain a mixture.
[0067] In this embodiment, the conductive agent particles and the binder are first mixed, and then the mixed intermediate is mixed with the active material particles. This method of adding and mixing helps the conductive agent particles to better adhere to the fibrous binder for distribution after fiberization, thereby helping to form a more ideal conductive network.
[0068] As an example, in the step of first mixing the conductive agent particles and the adhesive, the linear speed of the stirring paddle is 5 to 20 m / s (for example, but not limited to, the linear speed is any one of 5 m / s, 10 m / s, 15 m / s and 20 m / s, or a range between any two of them), the stirring time is 20 to 60 min (for example, but not limited to, the stirring time is any one of 20 min, 30 min, 40 min, 50 min and 60 min, or a range between any two of them), and the processing temperature is 5 to 20°C (for example, but not limited to, the processing temperature is any one of 5°C, 10°C, 15°C and 20°C, or a range between any two of them).
[0069] In this embodiment, in the step of mixing the conductive agent and the adhesive, the linear velocity of the stirring paddle, the stirring time and the processing temperature are respectively limited within specific ranges so that the conductive agent can be more evenly distributed in the adhesive.
[0070] It should be noted that the step of adding active material particles to the mixed material intermediate and mixing them can also be carried out by referring to the step of mixing conductive agent particles and binder.
[0071] As an example, in the fiberization treatment step, the linear speed of the stirring paddle is ≥40m / s (for example, but not limited to, the linear speed is any one of 40m / s, 42m / s, 45m / s, 47m / s and 50m / s, or a range between any two of them), the stirring time is 5 to 30min (for example, but not limited to, the stirring time is any one of 5min, 10min, 20min and 30min, or a range between any two of them), and the treatment temperature is 60 to 80°C (for example, but not limited to, the treatment temperature is any one of 60°C, 65°C, 70°C, 75°C and 80°C, or a range between any two of them).
[0072] In this embodiment, in the fiberization step, the linear speed of the stirring paddle, the stirring time and the treatment temperature are respectively limited within specific ranges to achieve a better fiberization effect of the adhesive.
[0073] As an example, in the crushing and granulation process, the screen specification in the crusher is 8 to 20 meshes, for example but not limited to any one of 8 meshes, 10 meshes, 12 meshes, 14 meshes, 16 meshes, 18 meshes and 20 meshes or a range between any two of them.
[0074] In this embodiment, in the crushing and granulation step, the specifications of the screen are limited to a specific range, which can take into account both good membrane surface quality and production continuity.
[0075] As an example, the steps of multi-roller continuous rolling film forming treatment include: firstly performing film forming treatment on the powder obtained after crushing and granulation treatment to obtain an electrode film precursor; then performing multiple thinning treatments on the electrode film precursor in sequence, wherein the roller gap in the multiple thinning treatments gradually decreases until the thickness of the membrane reaches a preset thickness specification, thereby obtaining a dry electrode electrode film.
[0076] In this embodiment, the thinning process is performed multiple times and the roller gaps of the multiple thinning processes are set to be gradually reduced, which helps to improve the thickness uniformity of the prepared electrode film.
[0077] It should be noted that the number of multiple thinning processes is not limited and can be adjusted according to actual needs. The embodiment of the present application takes three thinning processes in sequence as an example.
[0078] It is understandable that the roller gap in the three thinning treatments is gradually reduced, and the specific roller gap size is not limited and can be adaptively adjusted according to actual needs.
[0079] It should be noted that the processes or steps not specifically described or limited in the method for preparing the dry electrode film can be arranged according to conventional selections in the art.
[0080] As an example, in the step of multi-roller continuous rolling film forming treatment, the rolling pressure of the film forming roller and the thinning roller is 5-7T, and the temperature of the film forming roller and the thinning roller is 140-160°C.
[0081] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0082] Example 1
[0083] The present invention provides a method for preparing a dry electrode film, comprising the following steps:
[0084] 1% of conductive carbon black (conductive agent) and 2% of polytetrafluoroethylene (binder) are mixed to obtain a mixed intermediate, wherein the linear speed of the stirring paddle is 20 m / s, the stirring time is 20 min, and the treatment temperature is 18°C; then 97% of lithium iron phosphate material particles (positive electrode active material) are added to the mixed intermediate and mixed, wherein the lithium iron phosphate material particles include 50% of large-size active material particles (D50 is 7.5 μm, D90 is 19 μm, and compaction density is 2.18 g / cm 3 ) and 50% of small-size active material particles (D50 is 1.2 μm, D90 is 4 μm, and compacted density is 2.57 g / cm 3 ) to obtain a mixture.
[0085] The mixed material is subjected to fiberization treatment in sequence, wherein the linear speed of the stirring paddle is 40 m / s, the stirring time is 15 min, and the treatment temperature is 65°C; the fiberized material is then subjected to crushing and granulation treatment, wherein the screen in the crusher is 10 mesh; the powder obtained after the crushing and granulation treatment is then subjected to film-forming treatment to obtain an electrode film precursor, wherein the temperature of the film-forming roller is 150°C, the roller gap is 280 μm, and the pressure of the film-forming roller is 6T; the electrode film precursor is then subjected to three thinning treatments in sequence, wherein the temperature of the thinning roller is 150°C, the pressure of the thinning roller is 6T, and the roller gaps of the three thinning treatments are 230 μm, 180 μm and 130 μm, respectively, to obtain a dry electrode electrode film.
[0086] Comparative Example 1
[0087] The embodiment of the present application provides a method for preparing a dry electrode film, which differs from Embodiment 1 only in that all lithium iron phosphate material particles are large-size active material particles.
[0088] Comparative Example 2
[0089] The embodiment of the present application provides a method for preparing a dry electrode film, which differs from Embodiment 1 only in that all lithium iron phosphate material particles are small-size active material particles.
[0090] Test Example 1
[0091] Electron microscope test of electrode film
[0092] Test method:
[0093] The electrode films prepared in Example 1 were numbered respectively, and then the microstructure of the samples was tested using an electron microscope.
[0094] See also Figure 2It can be seen that according to the preparation process provided in the embodiment of the present application, in the prepared electrode film, the adhesive is fibrous and the small-size active material particles are arranged in the area close to and bonded to the adhesive along the extension direction of the adhesive, wherein some small particles of a specific particle size close to the adhesive are filled in the gaps between the large particles, and the small particles of a specific particle size attached to the adhesive can surround the large particles together with the fibrous adhesive.
[0095] Test Example 2
[0096] Performance test of electrode film
[0097] Test method:
[0098] The electrode films prepared in Example 1 and Comparative Examples 1 and 2 were numbered respectively, and then the tensile strength and compaction density of each sample were tested and statistically reported in Table 1;
[0099] The test steps for tensile strength are as follows: cut each sample electrode film separately to obtain a tensile sample with a width of 6 mm, and then use a tensile testing machine to clamp both sides of each tensile sample and perform a tensile test on it, wherein the tensile speed is 250 mm / min, until the tensile sample breaks, and record the tensile strength at the time of break.
[0100] The test steps for compaction density are as follows: cut each sample electrode film into cylindrical samples with a diameter of 12 mm, then test the weight of each cylindrical sample, first calculate the surface density, and then calculate the compaction density based on the surface density and the corresponding thickness.
[0101] Table 1
[0102] sample Tensile strength(Mpa) <![CDATA[Compaction density (g / cm 3 )]]> Example 1 0.26 2 Comparative Example 1 0.263 1.55 Comparative Example 2 0.16 1.96
[0103] Referring to Table 1, it can be seen from the test results of Example 1 and Comparative Examples 1-2 that the electrode film prepared by the preparation process provided in the embodiment of the present application can have both good film-forming properties and high compaction density.
[0104] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A dry electrode film, characterized in that: The invention comprises active material particles, conductive agent particles and adhesive, wherein the adhesive is in fibrous form, the active material particles comprise large-size active material particles and small-size active material particles, the particle size D50 of the large-size active material particles is 4 to 10 μm, the particle size D50 of the small-size active material particles is 1 to 2 μm, and the small-size active material particles are arranged in an area close to and bonded to the adhesive along the extension direction of the adhesive.
2. The dry electrode film according to claim 1, characterized in that: The particle size D50 of the large-size active material particles is 6 to 8 μm, and the particle size D50 of the small-size active material particles is 1 to 1.5 μm.
3. The dry electrode film according to claim 2, characterized in that: The particle size D90 of the large-size active material particles is 15 to 20 μm, and the particle size D90 of the small-size active material particles is 3 to 4 μm.
4. The dry electrode film according to any one of claims 1 to 3, characterized in that: The mass of the small-size active material particles directly bonded to the binder accounts for 50 to 60% of the total mass of the small-size active material particles.
5. The dry electrode film according to any one of claims 1 to 3, characterized in that: In the active material particles, the mass ratio of the large-size active material particles to the small-size active material particles is (10-50):(50-90).
6. The dry electrode film according to any one of claims 1 to 3, characterized in that: In the electrode film, the mass ratios of the active material particles, the conductive agent particles and the binder are (90-98): (1-3): (2-5) respectively.
7. The dry electrode film according to any one of claims 1 to 3, characterized in that: The active material particles are positive electrode active material particles, and the positive electrode active material particles are selected from at least one of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel-manganese or nickel-aluminum binary materials and nickel-cobalt-manganese-aluminum quaternary materials.
8. The dry electrode film according to any one of claims 1 to 3, characterized in that: The conductive agent particles are selected from at least one of carbon nanotubes, conductive carbon black, carbon fibers, conductive graphite and acetylene black; And / or, the adhesive is selected from at least one of polyvinylidene fluoride and polytetrafluoroethylene.
9. A method for preparing a dry electrode film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The active material particles, the conductive agent particles and the adhesive are mixed to obtain a mixture; and the mixture is subjected to a fiberization treatment, a crushing and granulation treatment and a multi-roller continuous rolling film-forming treatment in sequence to obtain the dry electrode plate film.
10. The preparation method according to claim 9, characterized in that: The step of mixing the active material particles, the conductive agent particles and the binder to obtain a mixture comprises: Firstly, the conductive agent particles and the adhesive are mixed to obtain a mixed material intermediate; The active material particles are added to the mixed material intermediate and mixed to obtain a mixed material.
11. The preparation method according to claim 10, characterized in that: In the step of first mixing the conductive agent particles and the adhesive, the linear speed of the stirring paddle is 5 to 20 m / s, the stirring time is 20 to 60 min, and the processing temperature is 5 to 20°C.
12. The preparation method according to claim 11, characterized in that: In the fiberization step, the linear speed of the stirring paddle is ≥40 m / s, the stirring time is 5 to 30 min, and the treatment temperature is 60 to 80°C.
13. The preparation method according to claim 9, characterized in that: In the crushing and granulation step, the screen size in the crusher is 8 to 20 meshes.
14. The preparation method according to claim 9, characterized in that: The multi-roller continuous rolling film forming process comprises: First, the powder obtained after the crushing and granulation treatment is subjected to a film-forming treatment to obtain a pole piece film precursor; then the pole piece film precursor is subjected to multiple thinning treatments in sequence, wherein the roller gap in the multiple thinning treatments is gradually reduced until the thickness of the membrane reaches a preset thickness specification, thereby obtaining the dry electrode pole piece film.
Citation Information
Patent Citations
High-lithium-ion-conduction positive plate and preparation method thereof
CN112086618A
Preparation method and application of electrode plate
CN114068857A
Dry-method pole piece and preparation method thereof
CN114709363A
All-solid-state battery and method for manufacturing same
CN115882047A
Dry electrode film, electrode including dry electrode film, and lithium battery including electrode
CN117438552A
Cited By
Mixing method of electrode material, preparation method of electrode diaphragm, battery pole piece, battery and electronic equipment
CN120545297A
